THE USE OF LICHENS FOR BIOMONITORING OF ATMOSPHERIC POLLUTION - (:unkn) unknown (YILDIZ TECHNICAL UNIV, 2015)
Although sulfur dioxide concentration decreased in recent years caused by the discouragement of fossil fuel, pollutants in the atmosphere still forming a considerable threat to human health, and it should be followed and taken constant and serious precautions about causing resources. Instantaneous or ongoing air pollution levels can be measured in various ways, directly or indirectly. In this study, to determine air quality (in terms of quantities and impacts of pollutants such as sulfur dioxide, heavy metals, radionuclides), how to benefit the lichens featuring bioindicators and biomonitors, which methods are applied, the advantages and disadvantages of biological methods, past to present studies on this subject in the world, the assessment of the relevant literature and the reliability of the obtained results were taken from a broad perspective. In addition, the text covers various complementary information on the subject such as environmental and anthropogenic factors which are effective on pollution sensitivity of lichens, adverse effects of pollution on lichen structure, metal uptake mechanism in lichen thallus and comparative analysis of data relating to changes in parameters in vitality of lichens. This review will be a guiding source for air quality biomonitoring with lichens today and creation of protection strategies.
Keywords: Air quality; bioindicator; biomonitor; lichen; HEAVY-METAL POLLUTION; AIR-POLLUTION; XANTHORIA-PARIETINA; CLADONIA-RANGIFORMIS; HYPNUM-CUPRESSIFORME; EPIPHYTIC LICHENS; TRACE-ELEMENTS; BARK PH; MOSSES; REGION